Breaking Habits: The Effect of the French Vending Machine Ban on School Snacking and Sugar Intakes. (30th October 2017) - Capacci, Sara; Mazzocchi, Mario; Shankar, Bhavani
Abstract: This paper estimates the effect of the 2005 vending machine ban in French secondary schools on nutrient intakes and on the frequency of morning snacking at school. Using data before and after the ban, and exploiting the discontinuity associated with the age‐dependent exposure to the ban, we specify a difference‐in‐differences regression discontinuity design. Since the relationship between age‐at‐interview and school level is not precise, we introduce fuzziness in the model. We find that the ban has generated a 10‐gram reduction in sugar intakes from morning snacks at school, and a significant reduction in the frequency of these morning snacks. However, we find no evidence that the intervention affects total daily intakes, and our results are suggestive of compensation effects.